Dias-Logan syndrome with a p.Leu360Profs*212 heterozygous pathogenic variant of in a Chinese patient: A case report - Yizhuo Shu; Xiaoling Chen; Zhuoqun Wei; Chunyue Chen (SAGE Open Medical Case Reports)
Dias-Logan syndrome, also known as intellectual developmental disorder with persistence of fetal hemoglobin (HbF), or BCL11A -related intellectual developmental disorder, is an extremely rare neurogenetic disorder characterized by intellectual disability (ID), delayed psychomotor development, variable dysmorphic features, and asymptomatic persistence of fetal hemoglobin. The prevalence and incidence of this condition are currently unknown. We report an 8-year-old Han Chinese male patient with Dias-Logan syndrome who carries a de novo heterozygous pathogenic variant, c.1078dupC (p.Leu360Profs*212), in the BCL11A gene, leading to ID and γ-globin suppression, identified through trio-based whole exome sequencing (trio-WES). All his blood parameters were normal except for an elevated HbF level, which was 19.9% of total hemoglobin. Given the negative family history for ID, epilepsy, and alcohol consumption, de novo inheritance was presumed. Consequently, trio-WES analysis (parents and child) was conducted as it can identify potential new causal variants in the offspring. So far, a comprehensive understanding of the phenotypic spectrum of Dias-Logan syndrome and the impact of genotypic variation on disease severity is still lacking. Therefore, our case report enriches the existing literature on the clinical spectrum and genotype–phenotype correlations of BCL11A -related syndrome and provides some helpful information for diagnosis, management, and genetic counseling.